Analisis penerapan lean six sigma terhadap pengendalian pemborosan material, waktu dan biaya berdasarkan kualifikasi perusahaan konstruksi di Jawa Barat - Gergorius Yohanes Iyai; Peter F. Kaming (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Application lean six sigma (LSS) in West Java is still more often used in the manufacturing industry, in order to provide good product quality for customer satisfaction. Therefore, this study aims to determine how far the application of LSS in West Java has been applied to the construction industry and to find out whether there are differences between each company's qualifications regarding how to control material waste, time waste and cost waste in construction projects after controlling LSS. The method used to answer the purpose of implementing LSS is a descriptive statistical test. While the methods used for different ways of controlling the wastage of materials, time and costs are Multivariate Analysis of Covariance (MANCOVA). The results of the descriptive statistical tests show that the application of LSS to large companies is included in the Very Good criteria (BS) with a score of 82%, for medium-sized companies it gets a value of 75% and small companies with a value of 74%, which means that its application is included in the Good criteria (B). The MANCOVA test results show that there is a difference between large and medium-sized companies in controlling material wastage. There is a difference between large and medium-sized companies in controlling time wastage. There is a difference between large companies and small companies in controlling time wastage. As for the wastage of costs, each company's qualifications in West Java do not have significant differences.